Nutrición infantil y su incidencia en el bajo rendimiento académico de los estudiantes de quinto año de educación básica de la Escuela Assad Bucaram. del recinto El Jazmin, Parroquia Baba, Cantón Baba, Provincia de Los Ríos - Aguilar Montes, Bertha del Rocio (2020)
The present research work on “Nutrition and its impact on the academic performance of the fifth year students of Basic Education of the“ Assad Bucaram ”school. The Jazmín campus, from the Baba parish, Baba canton, province of Los Ríos, was developed to learn that students are not well fed and consequently their academic performance will be low. To study the incidence of nutrition in the academic performance of students, that is, to be aware that adequate food will help to have the energy necessary to fulfill the different activities of the classroom. With the preparation and application of surveys aimed at students and teachers, a qualitative and quantitative analysis of the data obtained could be made, and conclusions and recommendations made. After analyzing the results of the surveys, the solution proposal is proposed; a manual on adequate food to improve children's academic performance, covering topics such as: nutritional needs, types of nutrients, what foods our three daily meals should contain, what are the food groups in the food pyramid and why it is important doing physical activity. As parents we must set the example by creating good eating habits to enjoy good health. At the conclusion of the investigation it was established that it is important to know that food is a fundamental factor that allows students to grow and develop healthily; food consumption depends on several factors: age, weight, height, school, leisure and social activities. Family and school level should be educated to encourage the consumption of foods of high nutritional value.